2020
DOI: 10.1371/journal.ppat.1008999
|View full text |Cite
|
Sign up to set email alerts
|

Chikungunya virus antagonizes cGAS-STING mediated type-I interferon responses by degrading cGAS

Abstract: Chikungunya virus (CHIKV) is a mosquito-borne alphavirus known to cause epidemics resulting in predominantly symptomatic infections, which in rare cases cause long term debilitating arthritis and arthralgia. Significant progress has been made in understanding the roles of canonical RNA sensing pathways in the host recognition of CHIKV; however, less is known regarding antagonism of CHIKV by cytosolic DNA sensing pathways like that of cyclic GMP-AMP synthase (cGAS) and Stimulator of Interferon Genes (STING). Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 96 publications
3
63
0
1
Order By: Relevance
“…Interestingly, similar to that of DENV NS3, the nuclear localization of CHIKV nsP2 also occurs temporarily during early infection, after which this protein resides in the cytoplasm [136]. IFN antagonism by nsP2 can be achieved by several mechanisms, including via a reduction in the cGAS level by a global translational inhibition [131,136], an inhibition of STAT1 activation and/or block of pY-STAT1 nuclear import [133], and a promotion of STAT1 nuclear export [132].…”
Section: Chikungunya Virus (Chikv)mentioning
confidence: 98%
See 1 more Smart Citation
“…Interestingly, similar to that of DENV NS3, the nuclear localization of CHIKV nsP2 also occurs temporarily during early infection, after which this protein resides in the cytoplasm [136]. IFN antagonism by nsP2 can be achieved by several mechanisms, including via a reduction in the cGAS level by a global translational inhibition [131,136], an inhibition of STAT1 activation and/or block of pY-STAT1 nuclear import [133], and a promotion of STAT1 nuclear export [132].…”
Section: Chikungunya Virus (Chikv)mentioning
confidence: 98%
“…A mutation of the CHIKV CP's NES near the N-terminus (aa residues 44-53) caused the retention of viral CPs in the nucleus and also blocked the host nuclear import system for unknown reasons [130]. CHIKV nsP2 inhibits the host IFN-induced antiviral response [131][132][133][134]. Although nsP2 lacks an NLS (reviewed in [135]), the nuclear import of nsP2 is necessary for suppressing the host antiviral response [134].…”
Section: Chikungunya Virus (Chikv)mentioning
confidence: 99%
“…154 Similarly, the CHIKV (Chikungunya virus) capsid protein suppressed transcription of IFN-β during CHIKV infection through inducing autophagy-dependent cGAS degradation. 155 Furthermore, the NSP1 protein from the RNA virus Zika stabilized caspase 1 to enhance cGAS cleavage and inactivation, leading to evasion of innate-immune sensing. 156 Together, these viral proteins through binding cGAS to guide cGAS for degradation (through proteasome, lysosome, and autophagy) or cleavage as an approach to facilitate evasion of host detection.…”
Section: Regulation Of Cgas Activation By Cgas-binding Proteinsmentioning
confidence: 99%
“…While single mutants were not sufficient for the phenotype, a double mutant sustaining S79C and L224I sufficiently exhibited an attenuated phenotype in vivo [ 28 ]. A recent study further demonstrated a role for nsP1 in regulating the IFN-I response by identifying the CHIKV-mediated degradation of the cytosolic DNA sensor cyclic GMP-AMP synthase (cGAS) and a direct interaction of nsP1 with stimulator of interferon genes (STING) that stabilizes nsP1 and increases palmitoylated nsP1 in vitro, a post-translational modification previously implicated as important in replication and pathogenesis in vivo [ 80 , 81 , 82 ]. Finally, key residues located at the SFV nsP1 P1/2 cleavage site have been shown to function together with residue 515 of nsP2 and drive neurovirulence in mice [ 83 ].…”
Section: Determinants Of Virulencementioning
confidence: 99%